Instructional Leadership For Excellent Schools A Site Study At High School 1 Sukorejo Kendal - Purwati, Eko (2012)
This study has four purposes, to describe the principal characteristics of`relationships with teachers and staff; the characteristics of a teacher with other teachers, the relationship characteristics of excellent school leadership, and the principal characteristics of social relationship with people around the school in High School 1 Sukorejo. It is a qualitative research by using ethnography approach due to it is the appropriate type of research to analyze social phenomena. Data were collected by interview, observation in school environment, and documentation, such as school profile. Data analysis was done by ethnography model, organizing file, reading the whole information, elaborating social setting and event observed, interpreting the outcomes, data display, and drawing conclusion. Data validity is objective by using in-depth interview, observation and data collection. The findings suggest that: 1) the principal characteristics of relationships with teachers and staff focuses on four pillars- planning, organizing, actuating, and controlling abbreviated POAC; the principal coordinates all elements of POAC to create the efficiency, in accordance with the functions and duties. The Principal motivates / organizes and involves teachers in quality improvement (human resource) to enhance their professional potential by further studies to Bachelor Degree l and Master Degree, joining training and seminar. 2) The relationship of a teacher with other teachers is based on the professionalism, familial and social solidarity, good background in the same or different expertise and do not consider seniority. 3) The relationship of principal leadership includes the relationship with teachers that is professional and familial, be able to accept input from teachers formally or personally, and has a conducive condition, so teachers can perform learning activities effectively and students can learn quietly. 4) The principal characteristics of social relationship include having the social competence to interact effectively with students, teachers, staff community, government at sub district level and district, as well as the committee. The principal social relationships become the key to success.